Reliability Assessment of Commercial Off-the-shelf Operating System Software: An Empirical Study - dos Santos, Caio Augusto Rodrigues; Antunes, Marcela; Matias Jr, Rivalino; Assunção, Lucas Miranda; Maciel, Vinicius (Anais do Simpósio Brasileiro de Engenharia de Sistemas Computacionais (SBESC); 2018: Anais do VIII Simpósio Brasileiro de Engenharia de Sistemas Computacionais, 2018)
According to the literature, the main cause of failures in computer systems are defects in software. Surveying the research works in software reliability, we observe that studies in reliability of operating system (OS) software are not abundant. Note that a computer system with highly reliable hardware and applications may not be dependable enough if its OS does not show an equivalent level of reliability. This paper presents an empirical study on the reliability of a commercial off-the-shelf OS software. We analyzed 5,351 records of real OS failures, collected from different computers and workplace environments. Based on the more frequent OS failures observed, we created reliability stochastic models to assess the sensitivity of the OS reliability with respect to these failures. The empirical evidence and analytical results show that the OS service of software update had the highest reliability importance, i.e., this is the OS component investigated whose improvement should be prioritized to have the greatest improvement on the OS reliability as a whole.